2010
DOI: 10.1099/mic.0.042010-0
|View full text |Cite
|
Sign up to set email alerts
|

A new macrocyclic antibiotic, fidaxomicin (OPT-80), causes less alteration to the bowel microbiota of Clostridium difficile-infected patients than does vancomycin

Abstract: A new macrocyclic antibiotic, fidaxomicin Clostridium difficile infection (CDI) is the most common identifiable cause of diarrhoea in hospitalized patients. Current therapies rely on the administration of metronidazole or vancomycin, which reduce vegetative populations of C. difficile in the bowel. Recurrence of the disease when treatment with these antibiotics ceases indicates that metronidazole and vancomycin affect not only C. difficile but also commensal populations that normally mediate competitive exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
146
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(157 citation statements)
references
References 14 publications
9
146
0
2
Order By: Relevance
“…In recent phase 3 clinical trials in patients with C. difficile infection, fidaxomicin not only was well tolerated and achieved the primary end point of clinical cure but also demonstrated a significantly lower rate of recurrence of infection compared with vancomycin (Crook et al, 2010;Louie et al, 2009b;Miller et al, 2009). Analysis of stool samples from subjects during a phase 2 doseranging study demonstrated that fidaxomicin not only lacks activity against Gram-negative bacteria but is also sparing of Gram-positive commensals (Louie et al, 2009a;Tannock et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent phase 3 clinical trials in patients with C. difficile infection, fidaxomicin not only was well tolerated and achieved the primary end point of clinical cure but also demonstrated a significantly lower rate of recurrence of infection compared with vancomycin (Crook et al, 2010;Louie et al, 2009b;Miller et al, 2009). Analysis of stool samples from subjects during a phase 2 doseranging study demonstrated that fidaxomicin not only lacks activity against Gram-negative bacteria but is also sparing of Gram-positive commensals (Louie et al, 2009a;Tannock et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…By altering the normal composition of the protective colonic microbial flora, antibiotic treatments create favourable conditions for colonization and hence infection by C. difficile (Wilson & Perini, 1988;Tannock et al, 2010). However, spores require the presence of certain compounds in order to undergo germination.…”
Section: Discussionmentioning
confidence: 99%
“…Ultima nata, inserita nella farmacopea italiana nel novembre 2013, fidaxomicina [61,[72][73][74][75][76][77][78] rappresenta la molecola antibatterica oggi più avanzata e moderna. La sua farmacodinamica è caratterizzata da un'azione diretta e mirata sul C. difficile con un ridotto impianto sul resto del microbiota intestinale, che pertanto ne risulta risparmiato e protetto.…”
Section: Introduzioneunclassified